(3GdYbO GdeaQO aj Mce GdCeQOs - (3CMeO Hf eMeO Hf jhfS, Uaj GdOjf GdOLGfj GdbTGTj,J (B1071 (3g` s
(3ChdgG (B:s
(3CeG HYO abO aTi ai gPG GdReGf GdPi jdYH GdTjWGf HCgdg deG QCjJ gPG GdCeQ GdaXjY ESJNQJ Gdehdi GdSejY ai LeY TF eeG hQO eSejkG dg GdYbO GdeaQO ai Mce GdCeQ s
(3BNQgG (B:s
(3ajG eScjf EPG cGfJ GdCQVJeJ GdQSGdI HMeO Gddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B170s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYi Mdje (B15) s
Keywords: (3Gdabg GdTGaYjs